(3EJMGa GdGcGHQ HGSfGO GdOaGJQs - (3, eMeO Hf Ydj Hf eMeO Hf YHO Gddg, CHh YHO Gddg GdThcGfj , J (B1250 (3g` s ((3HghjGd s)
(3ChdgG (B:s
(3hHYO aEf Gddg SHMGfg deG ef Ydi HdbGA eTGjN GYdGe GNPJ Yfge HGdSeGY hGdELGRI dHYV eUfaGJ Ggd GdGSdGe QZHJ Edi LeY eG GQhjg Yfge ef GdeUfaGJ ai gPg GdhQjbGJ hSejJ gPG GdeNJUQ GJMGa GdGcGHQ HESfGO GdOaGJQ s
(3BNQgG (B:s
(3GdjhGbjJ djMi Hf CMeO MfT GQhjI HGdESfGO GdeJbOe Edi GdGeGe GdegOi CMeO Hf jMji ai GdGRgGQ hGdHMGQ Yf GdbGSe Hf CMeO MejO Yf GHjg Yf GdeDda QMeg Gddg hEdi gfG GfJgi eG bUOJ LeYg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HBNQgG CLGRGJ cKjQIs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs